2013
DOI: 10.3390/d5030680
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Analysis of Life within a Former Subglacial Lake Sediment in Antarctica

Abstract: Abstract:Since the first descriptions of Antarctic subglacial lakes, there has been a growing interest and awareness of the possibility that life will exist and potentially thrive in these unique and little known environments. The unusual combination of selection pressures, and isolation from the rest of the biosphere, might have led to novel adaptations and physiology not seen before, or indeed to the potential discovery of relic populations that may have become extinct elsewhere. Here we report the first mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 74 publications
2
11
0
Order By: Relevance
“…After 16 months of simulated warming, a net decrease of Proteobacteria, Acidobacteria, and Planctomycetes were observed across all three soil samples indicating that they were highly affected by increased temperature. The results agree with previous studies by Mateos-Rivera et al (2016), Pearce et al (2013), and Schuette et al (2010) that stated Proteobacteria decreases with higher incubation temperatures. Skidmore et al (2005) suggested that Proteobacteria decreases with increasing temperature, as some of the members are adapted to live in lower temperature habitats with low organic matter content.…”
Section: Discussionsupporting
confidence: 93%
“…After 16 months of simulated warming, a net decrease of Proteobacteria, Acidobacteria, and Planctomycetes were observed across all three soil samples indicating that they were highly affected by increased temperature. The results agree with previous studies by Mateos-Rivera et al (2016), Pearce et al (2013), and Schuette et al (2010) that stated Proteobacteria decreases with higher incubation temperatures. Skidmore et al (2005) suggested that Proteobacteria decreases with increasing temperature, as some of the members are adapted to live in lower temperature habitats with low organic matter content.…”
Section: Discussionsupporting
confidence: 93%
“…Actinobacteria from a low water activity area of Antarctica (similar to the situation in deserts) are also described. The bacterial diversity of Lake Hodgson, the Antarctic Peninsula, was recognized as 23% Actinobacteria , 21% Proteobacteria , 20.2% Plantomycetes , and 11.6% Chlorofllexi (Pearce et al, 2013 ), while from Antarctic Dry Valley soil Cyanobacteria (13%), Actinobacteria (26%), and Acidobacteria (16%) represented the majority of the identified resident bacteria (Smith et al, 2006 ). Culture-independent survey of multidomain bacterial diversity in the cold desert of the McKelvey Valley demonstrated that highly specialized communities colonize in distinct lithic niches occurring concomitantly within this ecosystem.…”
Section: Xerophilic Strains Isolated From Arid Areasmentioning
confidence: 99%
“…Grímsvötn Lake yields bacterial cell counts of approximately 10 4 per millilitre under 300 m of ice [ 42 ]; Skaftárketill Lake yields up to 5×10 5 bacterial cells per millilitre [ 43 ]. High cell densities have been found in subglacial sediments in several other regions, including the Alps [ 44 ], New Zealand [ 45 ], the Canadian High Arctic [ 46 ], Svalbard [ 47 ], the Antarctic Peninsula [ 48 ] and the West Antarctic Ice Sheet [ 37 ].
Figure 3.
…”
Section: The Special Case Of the Sub-ice Deep Biospherementioning
confidence: 99%